Probing the local, electronic and magnetic structure of matter under extreme conditions of temperature and pressure. Issue 3 (2nd July 2016) - Torchio, R.; Boccato, S.; Cerantola, V.; Morard, G.; Irifune, T.; Kantor, I.
ABSTRACT: In this paper we present recent achievements in the field of investigation of the local, electronic and magnetic structure of the matter under extreme conditions of pressure and temperature. These results were obtained thanks to the coupling of a compact laser heating system to the energy-dispersive XAS technique available on the ID24 beamline at the ESRF synchrotron. The examples chosen concern the melting and the liquid structure of 3d metals and alloys under high pressures (HPs) and the observation of temperature-induced spin crossover in FeCO3 at HP.